A phosphogypsum-based filling body, a preparation method and application thereof
Patent Information
- Application Number
- CN202611176328.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]专利CN104211313B公开一种由磷石膏、赤泥、磷渣、普通硅酸盐水泥熟料复配而成的矿山充填胶凝体系,该体系需额外掺入硅酸盐水泥熟料作为水化核心组分,熟料生产能耗高、碳排放大,大幅提升充填材料制备成本
(1)利用磷石膏基胶凝材料替代水泥制备充填体,实现了磷石膏与尾矿的协同大规模处置。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to fillers and their preparation methods, and more specifically to a phosphogypsum-based filler, its preparation method, and its application. Background Technology
[0002] Cemented backfilling of mined-out areas is a core technology for achieving green mining, eliminating geological hazards in mined-out areas, and disposing of industrial solid waste on a large scale. It aligns with multiple national policy guidelines for solid waste resource utilization, ecological environmental protection, and safe mine production.
[0003] Traditional silicate cement-based backfill materials mostly focus on basic mechanical properties such as early compressive strength to meet short-term downhole support needs, but they suffer from many technical shortcomings, including low solid waste utilization, insufficient durability, high risk of heavy metal leaching, and high production costs. Existing research has confirmed that phosphogypsum, rich in sulfate components, can serve as a high-quality sulfate activator, effectively stimulating the cementitious activity of industrial wastes such as slag and steel slag. The mechanical properties of the prepared phosphogypsum-based cementitious materials are comparable to those of traditional silicate cement, making it a superior technological path to replace cement and realize solid waste resource utilization.
[0004] Patent CN104211313B discloses a mine backfill cementitious system composed of phosphogypsum, red mud, phosphorus slag, and ordinary silicate cement clinker. This system requires the additional addition of silicate cement clinker as a core hydration component. The clinker production has high energy consumption and large carbon emissions, which significantly increases the cost of backfill material preparation.
[0005] Patent CN114133199A uses hemihydrate phosphogypsum, phosphorus slag powder, slag powder and quicklime to construct a geopolymer filling material. The core substrate of this system is hemihydrate phosphogypsum, which has fundamentally different physicochemical properties and hydration reaction mechanism from dihydrate phosphogypsum produced by the mainstream wet process phosphoric acid in China. It is difficult to adapt to the dihydrate phosphogypsum solid waste of most phosphate fertilizer companies.
[0006] In summary, existing technologies mostly focus on the short-term mechanical strength indicators of the filling body during the formulation design stage, without focusing on durability performance optimization design for long-term service conditions in deep mines, and without establishing a stable solidification mechanism for harmful components such as heavy metals and free phosphorus and fluorine. Long-term seepage of groundwater in mines will cause heavy metals and soluble impurities to be continuously dissolved, posing a risk of water and soil pollution. It is difficult to meet the dual needs of industrial solid waste resource utilization and long-term ecological safety in mines.
[0007] Therefore, there is a need for a novel phosphogypsum-based filler, its preparation method, and its application. Summary of the Invention
[0008] The purpose of this invention is to provide a phosphogypsum-based backfill material, its preparation method, and its application. The backfill material is prepared by phosphogypsum in conjunction with tailings. By optimizing the proportion of solid waste raw materials, constructing a composite activated cementitious system, and compounding a special durable modified composite additive, the pore structure and hydration product system of the backfill material are precisely optimized. This simultaneously achieves efficient disposal of two types of bulk industrial solid waste, improves the mechanical properties of the backfill material, enhances its long-term durability and stability, and solidifies harmful heavy metal components. This effectively overcomes the defects of existing technologies and meets the dual requirements of long-term safe service and ecological environmental protection of mine backfill materials in complex underground environments.
[0009] The technical solution of the present invention is as follows: A phosphogypsum-based filler is composed of multiple solid wastes, aggregates, composite additives, and mixing water. By weight, the multiple solid wastes include 50-70 parts modified phosphogypsum, 15-25 parts blast furnace slag, 10-17 parts steel slag, and 5-8 parts calcium carbide slag.
[0010] Preferably, the aggregate is 420 to 580 parts by weight, and the composite admixture is 0.8% to 2.0% of the phosphogypsum-based cementitious material.
[0011] According to one embodiment of the present invention, the composite admixture includes low-modulus water glass, silica fume, and polycarboxylate superplasticizer.
[0012] Preferably, the low-modulus water glass accounts for 0.4% to 1.0% of the total amount of the composite admixture, the silica fume accounts for 0.3% to 0.7% of the total amount of the composite admixture, and the polycarboxylate superplasticizer accounts for 0.1% to 0.3% of the total amount of the composite admixture.
[0013] According to one embodiment of the present invention, the modified phosphogypsum is prepared by: placing wet phosphogypsum into a neutralization stirring tank, adding quicklime to neutralize the free acid to pH=7.0-8.2, and then piling it up for pre-dehydration until the moisture content is below 10% to obtain modified phosphogypsum.
[0014] Preferably, the aggregate is tailings, and the tailings are selected from one or more of copper tailings, lead-zinc tailings, or gold tailings.
[0015] Preferably, the mixing water is selected from one or more of tap water, underground circulating wastewater, or surface water.
[0016] A method for preparing a phosphogypsum-based filler as described above includes the following steps: S1: Modified phosphogypsum, blast furnace slag, steel slag and carbide slag are dried, ground and then mixed evenly to obtain phosphogypsum-based cementitious material. S2: In the phosphogypsum-based cementitious material obtained in step S1, aggregates, composite additives, and mixing water are added in proportion, mixed and stirred evenly to obtain the filling body. Preferably, by weight, the phosphogypsum-based cementitious material is 100 parts, the aggregate is 420-580 parts, the composite admixture is 0.8%-2.0% of the phosphogypsum-based cementitious material, and the mixing water is 200-360 parts.
[0017] Preferably, in step S1, the modified phosphogypsum, blast furnace slag, steel slag, and... Calcium carbide slag is ground to a specific surface area ≥ 420 m² 2 / kg.
[0018] Preferably, in step S1, the drying temperature is 100-110°C, and the product is dried to a constant weight.
[0019] Preferably, the aggregate is tailings. When the proportion of fine particles in the tailings exceeds 50%, an appropriate amount of the modified phosphogypsum is added to control the proportion of fine particles to 25%~48%.
[0020] When the tailings are wet tailings, the wet tailings are concentrated and dehydrated until the moisture content is less than 10%.
[0021] The aggregate is tailings. When the proportion of fine particles in the tailings exceeds 50%, an appropriate amount of modified phosphogypsum is added to control the proportion of fine particles to 25%~48%. By adding phosphogypsum, the proportion of fine particles can be reduced, and the fine particles in the tailings can not exceed 75%.
[0022] Application of a phosphogypsum-based filler, said phosphogypsum-based filler for use in mine backfilling.
[0023] The technical solution of the present invention has the following advantages: (1) By using phosphogypsum-based cementitious materials to replace cement in the preparation of filling materials, the synergistic large-scale disposal of phosphogypsum and tailings was realized.
[0024] (2) By adding composite additives, the hydration heat release rate of the cementitious material can be adjusted, the dispersibility can be increased, and the later shrinkage compensation of the filling body can also be provided.
[0025] (3) Through a multi-path synergistic durability enhancement mechanism, including optimizing the proportion of solid waste raw materials, constructing a composite activating gelation system, and compounding special durability-modifying composite additives, the pore structure and hydration product system of the filling body are precisely optimized, significantly improving the long-term durability and stability of the filling body, ensuring the long-term safety of the filling project, avoiding secondary pollution, and meeting the dual requirements of long-term safe service and ecological environmental protection of mine filling bodies in complex underground environments. Detailed Implementation
[0026] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0027] This invention provides a phosphogypsum-based filler, which is composed of multi-component solid waste, aggregate, composite additive, and mixing water. By weight, the multi-component solid waste includes 50-70 parts modified phosphogypsum, 15-25 parts blast furnace slag, 10-17 parts steel slag, and 5-8 parts carbide slag; the aggregate is 45-55 parts; and the composite additive accounts for 0.8%-2.0% of the total weight of the solid phase.
[0028] The composite admixture includes low-modulus water glass, silica fume, and polycarboxylate superplasticizer, wherein the low-modulus water glass accounts for 0.4% to 1.0% of the total amount of the composite admixture, the silica fume accounts for 0.3% to 0.7% of the total amount of the composite admixture, and the polycarboxylate superplasticizer accounts for 0.1% to 0.3% of the total amount of the composite admixture.
[0029] The present invention also provides a method for preparing a phosphogypsum-based filler, comprising the following steps: S1: Modified phosphogypsum, blast furnace slag, steel slag and carbide slag are dried, ground and then mixed evenly to obtain phosphogypsum-based cementitious material. S2: In the phosphogypsum-based cementitious material obtained in step S1, aggregates, composite additives and mixing water are added in proportion, mixed and stirred evenly to obtain the filling body.
[0030] The functions and principles of each component in this invention are as follows: This invention utilizes phosphogypsum to provide SO4 2- Sulfate activation and OH- alkali activation provided by carbide slag doubly activate the aluminosilicate activity in slag powder and steel slag powder, generating a large amount of CSH gel to fill the aggregate voids, and needle-like ettringite interlacing to form a dense skeleton; at the same time, the gel products formed by the hydration of slag and steel slag have excellent ion exchange and adsorption encapsulation capabilities, which can stabilize and seal free heavy metal ions, soluble phosphorus and fluoride ions in phosphogypsum and tailings through the dual effects of lattice replacement and physical coating, greatly reducing the risk of leaching of harmful components.
[0031] This invention adjusts the amount of tailings and phosphogypsum added based on the particle size distribution of the tailings, avoiding excessive fine powder and optimizing the packing density of the backfill, thereby achieving high durability from the aggregate skeleton. The dense and continuous aggregate skeleton can significantly reduce the interconnected pores inside the backfill, block the seepage channels of groundwater, and reduce the leaching of harmful ions such as heavy metals and soluble phosphorus and fluorine from a physical perspective.
[0032] In the composite admixture, the low-modulus water glass and water-reducing agent can regulate the hydration heat release rate and avoid stress caused by concentrated heat release; the water-reducing agent and silica fume can increase dispersibility, ensure sufficient hydration, and provide compensation for later shrinkage; the low-modulus water glass can also promote silica fume hydration and optimize the pore structure. Through the synergistic effect of these three substances, the hydration heat release rate of the cementitious material can be regulated, the dispersibility of the cementitious material can be increased, and compensation for later shrinkage of the filling body can be provided; sufficient hydration and shrinkage compensation can synergistically construct a dense matrix, thereby further inhibiting the leaching of harmful ions.
[0033] This invention utilizes a multi-path synergistic durability enhancement mechanism. It constructs a dense aggregate skeleton through raw material gradation structure optimization, builds a high-strength gel composite matrix through bidirectional stimulating hydration reaction, and supplements the composite admixture with microscopic regulation of pore structure and volume deformation to form a multi-layered durability assurance system of "dense aggregate skeleton + dense hydration products + stable microstructure". Example 1
[0034] (1) Composition of phosphogypsum-based cementitious material: 60 parts modified phosphogypsum, 20 parts blast furnace slag, 13 parts steel slag, and 7 parts carbide slag; Modified phosphogypsum pretreatment: wet phosphogypsum is neutralized to pH=7.5 with quicklime, and then stockpiled for pre-dehydration to a moisture content of 9.2%; (2) Aggregate: Copper tailings, with fine particles accounting for 62%, and modified phosphogypsum is added to adjust the overall fine particle composition to 36%; (3) Composite admixture: 0.6% low modulus water glass, 0.4% silica fume, and 0.3% polycarboxylate superplasticizer are compounded together; (4) Phosphogypsum-based filler: 100 parts phosphogypsum-based cement, 500 parts aggregate, 260 parts water, and 1.3% composite admixture.
[0035] S1: Modified phosphogypsum, blast furnace slag, steel slag, and carbide slag were dried at 105℃ to constant weight, and then ground separately to a specific surface area of 450 m². 2 / kg, then mix evenly to obtain phosphogypsum-based cementitious material; S2: In the phosphogypsum-based cementitious material obtained in step S1, aggregates, composite additives and tap water are added in proportion, mixed and stirred evenly to obtain the filling body. Example 2
[0036] (1) Composition of phosphogypsum-based cementitious material: 63 parts modified phosphogypsum, 17 parts blast furnace slag, 15 parts steel slag, and 5 parts carbide slag; Modified phosphogypsum pretreatment: wet phosphogypsum is neutralized to pH=7.5 with quicklime, and then stockpiled for pre-dehydration to a moisture content of 9.2%; (2) Aggregate: lead-zinc tailings, with fine particles accounting for 42%; (3) Composite admixture: 0.4% low modulus water glass, 0.7% silica fume, and 0.2% polycarboxylate superplasticizer are compounded together; (4) Phosphogypsum-based filler: 100 parts phosphogypsum-based cement, 500 parts aggregate, 260 parts water, and 1.3% composite admixture.
[0037] S1: Modified phosphogypsum, blast furnace slag, steel slag, and carbide slag are dried at 110℃ to constant weight, and then ground separately to a specific surface area of 450 m². 2 / kg, then mix evenly to obtain phosphogypsum-based cementitious material; S2: In the phosphogypsum-based cementitious material obtained in step S1, aggregates, composite additives and tap water are added in proportion, mixed and stirred evenly to obtain the filling body. Example 3
[0038] (1) Composition of phosphogypsum-based cementitious material: 50 parts modified phosphogypsum, 25 parts blast furnace slag, 17 parts steel slag, and 8 parts carbide slag; Modified phosphogypsum pretreatment: wet phosphogypsum is neutralized to pH=7.0 with quicklime, and then pre-dehydrated in stockpiles to a moisture content of 6.1%; (2) Aggregate: Gold tailings, with fine particles accounting for 25%; (3) Composite admixture: 0.4% low modulus water glass, 0.3% silica fume, and 0.1% polycarboxylate superplasticizer are compounded together; (4) Phosphogypsum-based filler: 100 parts phosphogypsum-based cement, 420 parts aggregate, 200 parts water, and 0.8% composite admixture.
[0039] S1: Modified phosphogypsum, blast furnace slag, steel slag, and carbide slag are dried at 100℃ to constant weight, and then ground separately to a specific surface area of 420 m². 2 / kg, then mix evenly to obtain phosphogypsum-based cementitious material; S2: In the phosphogypsum-based cementitious material obtained in step S1, aggregates, composite additives and tap water are added in proportion, mixed and stirred evenly to obtain the filling body. Example 4
[0040] (1) Composition of phosphogypsum-based cementitious material: 70 parts modified phosphogypsum, 15 parts blast furnace slag, 10 parts steel slag, and 5 parts carbide slag; Modified phosphogypsum pretreatment: wet phosphogypsum is neutralized to pH=8.2 with quicklime, and then stockpiled for pre-dehydration to a moisture content of 9.9%; (2) Aggregate: lead-zinc tailings, with fine particles accounting for 48%; (3) Composite admixture: 1.0% low modulus water glass, 0.7% silica fume, and 0.3% polycarboxylate superplasticizer are compounded; (4) Phosphogypsum-based filler: 100 parts phosphogypsum-based cement, 580 parts aggregate, 360 parts water, and 2.0% composite admixture.
[0041] S1: Modified phosphogypsum, blast furnace slag, steel slag, and carbide slag were dried at 110℃ to constant weight, and then ground separately to a specific surface area of 425 m². 2 / kg, then mix evenly to obtain phosphogypsum-based cementitious material; S2: In the phosphogypsum-based cementitious material obtained in step S1, aggregates, composite additives and tap water are added in proportion, mixed and stirred evenly to obtain the filling body.
[0042] Comparative Example 1 The difference between this comparative example and Example 1 is that there is no carbide slag in this comparative example.
[0043] Comparative Example 2 The difference between this comparative example and Example 1 is that no composite additives are used in this comparative example, and 1.3% polycarboxylate superplasticizer is used.
[0044] Comparative Example 3 The difference between this comparative example and Example 1 is that copper tailings with a fine particle ratio of 62% are used as aggregate in this comparative example.
[0045] Comparative Example 4 The difference between this comparative example and Example 1 is that the modified phosphogypsum in this comparative example is 80 parts, blast furnace slag is 10 parts, steel slag is 7 parts, and calcium carbide slag is 3 parts.
[0046] Comparative Example 5 The difference between this comparative example and Example 1 is that the modified phosphogypsum in this comparative example is 30 parts, blast furnace slag is 35 parts, steel slag is 25 parts, and calcium carbide slag is 10 parts.
[0047] Performance Testing: Performance tests were conducted on the filling bodies prepared in Examples 1, 2, 3, 4, Comparative Examples 1, 2, 3, 4, and 5. Specifically, the bleeding rate was determined according to the method described in National Standard GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures"; the 28-day drying shrinkage rate was determined according to the method described in National Standard GB / T 50082-2024 "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete"; the heavy metal leaching was determined according to the method described in Industry Standard HJ / T 299-2007 "Leaching Toxicity of Solid Waste - Sulfuric Acid and Nitric Acid Method"; and the permeability coefficient was determined according to the method described in National Standard GB / T 47546-2026 "Test Methods for Performance of Permeable Concrete". The obtained test data are shown in Table 1 below.
[0048] Table 1 Test Data
[0049] As shown in Table 1, Comparative Example 1 (excluding the carbide slag alkaline activation component), Comparative Example 2 (excluding the composite admixture), and Comparative Example 3 (without fine particle size control) all exhibited significantly increased values in early-stage bleeding, 28-day drying shrinkage, and permeability coefficient of the backfill material. This indicates that the backfill material prepared in Comparative Examples 1-3 had significantly reduced structural density, resulting in a significant increase in the leaching of harmful ions. This demonstrates that the present invention utilizes phosphogypsum to provide SO4. 2- The dual activation of sulfate and OH-alkali activation provided by carbide slag, the synergistic regulation of ternary composite additives, and the fine particle size distribution regulation significantly enhance the stability of the backfill and solidify the harmful heavy metal components.
[0050] Comparative Examples 4 and 5 adjusted the proportions of the modified phosphogypsum, blast furnace slag, steel slag, and carbide slag. After deviating from the raw material proportion range of the present invention, the durability of the filling material was significantly reduced, indicating that the raw material proportion range defined by the present invention can significantly improve the durability of the filling material.
[0051] Therefore, the filling material prepared according to the technical solution of the present invention has a precisely optimized pore structure, improved mechanical properties, enhanced long-term durability and stability, and solidified heavy metal harmful components, which can meet the dual requirements of long-term safe service and ecological environmental protection of mine filling materials in complex underground environments.
[0052] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A phosphogypsum-based filler, characterized in that, It is composed of multiple solid wastes, aggregates, composite additives and mixing water. By weight, the multiple solid wastes include 50-70 parts of modified phosphogypsum, 15-25 parts of blast furnace slag, 10-17 parts of steel slag and 5-8 parts of calcium carbide slag.
2. The filling body according to claim 1, characterized in that, The aggregate is 420 to 580 parts by weight, and the composite admixture is 0.8% to 2.0% of the phosphogypsum-based cementitious material.
3. The filling body according to claim 1 or 2, characterized in that, The composite admixture includes low-modulus water glass, silica fume, and polycarboxylate superplasticizer.
4. The filling body according to claim 3, characterized in that, The low-modulus water glass accounts for 0.4% to 1.0% of the total amount of the composite admixture, the silica fume accounts for 0.3% to 0.7% of the total amount of the composite admixture, and the polycarboxylate superplasticizer accounts for 0.1% to 0.3% of the total amount of the composite admixture.
5. The filling body according to any one of claims 1-4, characterized in that, The modified phosphogypsum is prepared by placing wet phosphogypsum in a neutralization mixing tank, adding quicklime to neutralize the free acid to pH=7.0-8.2, and then piling it up for pre-dehydration until the moisture content is below 10% to obtain modified phosphogypsum.
6. The filling body according to any one of claims 1-5, characterized in that, The aggregate is tailings, which are selected from one or more of copper tailings, lead-zinc tailings, or gold tailings.
7. The filling body according to any one of claims 1-6, characterized in that, The mixing water is selected from one or more of tap water, underground circulating wastewater, or surface water.
8. A method for preparing a phosphogypsum-based filler as described in any one of claims 1-7, characterized in that, Includes the following steps: S1: Modified phosphogypsum, blast furnace slag, steel slag and carbide slag are dried, ground and then mixed evenly to obtain phosphogypsum-based cementitious material. S2: In the phosphogypsum-based cementitious material obtained in step S1, aggregates, composite additives and mixing water are added in proportion, mixed and stirred evenly to obtain the filling body.
9. The preparation method according to claim 8, characterized in that, By weight, the phosphogypsum-based cementitious material comprises 100 parts, the aggregate comprises 420-580 parts, the composite admixture comprises 0.8%-2.0% of the phosphogypsum-based cementitious material, and the mixing water comprises 200-360 parts.
10. The preparation method according to claim 8 or 9, characterized in that, In step S1, the modified phosphogypsum, blast furnace slag, steel slag, and carbide slag are ground to a specific surface area ≥ 420 m². 2 / kg.
11. The preparation method according to any one of claims 8-10, characterized in that, In step S1, the drying temperature is 100-110℃, and the product is dried to a constant weight.
12. The preparation method according to any one of claims 8-11, characterized in that, The aggregate is tailings. When the proportion of fine particles in the tailings exceeds 50%, an appropriate amount of the modified phosphogypsum is added to control the proportion of fine particles to 25%~48%.
13. The application of a phosphogypsum-based filler as claimed in any one of claims 1-7, characterized in that, The phosphogypsum-based filler is used for mine backfilling.
Citation Information
Patent Citations
A phosphogypsum-based cementitious material and its application in mine tailings filling
CN104211313B